"The longest way round is the shortest way home": an overhaul of surgical ward rounds - Shetty,K; Poo,SXW; Sriskandarajah,K; Sideris,M; Malietzis,G; Darzi,A; Athanasiou,T (World Journal of Surgery, 2017)
BACKGROUND: Ward rounds, a keystone of hospital surgical practice, have recently been under the spotlight. Poor-quality ward rounds can lead to a greater number of adverse events, thereby cascading to an increased financial strain on our already burdened healthcare systems. Faced with mounting pressures from both outside and inside health organizations, concerted efforts are required to restore it back into prominence where it can no longer take a backseat to the other duties of a surgeon. METHODS: The nucleus of this narrative review is derived from an extensive literature search on surgical ward rounds. RESULTS: In this review, we focus on the need for reforms, current characteristics of surgical ward rounds, obstacles encountered by competing interests and proposed solutions in delivery of effective ward rounds that can meet with newly laid guidelines. CONCLUSION: Ward rounds should be standardized and prioritized to improve patient care.